Faktor-Faktor Penyebab Kurangnya Motivasi Belajar Peserta Didik dalam Mata Pelajaran PAI di Sekolah Negeri - Nabilah, Jihan; Akbar Romadlon, Dzulfikar (PAI RAFAH, 2024)
Motivation to learn plays a very important role in the learning process and the success of the learning process. A student will more easily be able to accept the material being taught when he has strong learning motivation, because apart from his obligation as a student to learn, he also has the desire to know and understand. material being taught. However, in fact, problems are still found related to the lack of student motivation to learn in Pai subjects. This research was conducted to determine the factors that cause students' learning motivation in Pai subjects to decrease or be low, the role of Pai teachers in increasing student learning motivation in Pai subjects and Pai teacher strategies in motivating student learning in Pai subjects as well as solutions to increase students' learning motivation. in PAI subjects. The research method used is qualitative research with a phenomenological approach. The subjects in this research were teachers and students.